Dietary Therapy of Crohn’s Disease: The IDI Synthesis - Monif, Gilles R. G. (Emerging Trends in Disease and Health Research Vol. 9, 2022)
In isolated cases of Crohn's disease, dietary changes have resulted in what biologics and steroids have yet to demonstrate: permanent remissions/cure. In Crohn’s disease, the induced alterations of gastrointestinal structure and function compromise the quantitative availability of vitamins, minerals and selected amino acids that are essential to optimum function of the immune system. The postulates advanced are 1) that clinical amelioration remissions achieved through dietary manipulation are the consequence of limiting MAP antigen/cytokine interactions at the sites of Mycobacterium avium subspecies paratuberculosis mucosal attachment and ultimately, 2) by dietary restoration and enhancement of host cellular immunity, resulting in the destruction of the MAP-template which drives the dysfunctional pro-inflammatory immune response. The relationship between diet and biologics is examined.